Ancient Greeks west and east - Tsetskhladze, Gocha R. (Mnemosyne, Supplements, 1999)
This volume deals with the concept of 'West' and 'East', as held by the ancient Greeks. Cultural exchange in Archaic and Classical Greece through the establishment of Hellenic colonies around the ancient world was an important development, and always a two-way process. To achieve a proper understanding of it requires study from every angle. All 24 papers in this volume combine different types of evidence, discussing them from every perspective: they are examined not only from the point of view of the Greeks but from that of the locals. The book gives new data, as well as re-examining existing evidence and reinterpreting old theories. The book is richly illustrated.